2000
DOI: 10.1063/1.1308109
|View full text |Cite
|
Sign up to set email alerts
|

The frequency-dependent depolarization ratio of the low-frequency Raman scattering of two inorganic systems in their glassy, supercooled, and molten states

Abstract: A temperature-dependent, low-frequency Raman study for a strong and a fragile glass-forming liquid is reported in order to elucidate the frequency and temperature sensitivity of the depolarization ratio spectrum, ρ(ω,T). Changes observed in ρ(ω,T) are directly reflected on the spectral features of the Raman coupling coefficient, Cαβ(ω). Our data provide evidence for polarization dependence of this coefficient, which has been completely overlooked in studies concerning the experimental determination of Cαβ(ω) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In other words, essentially the same band shape is obtained in the low-frequency range for polarized, depolarized, or without polarization selection of the scattered radiation. It is worth noting that the frequency-dependent depolarization ratio has been found in Raman spectra of high temperature molten salts, especially when complex molecular-like structures occur in the melt. ,, In the case of ionic liquids, the intermolecular vibrational dynamics has been much more investigated by OKE than low-frequency Raman spectroscopy. Both OKE and Raman spectroscopies probe polarizability fluctuations resulting from the molecular dynamics of the liquid, so that the spectral pattern of χ″(ω) is the same as the OKE spectra of ionic liquids.…”
Section: Vibrational Spectroscopy Of Pure Ionic Liquids In the Low-fr...mentioning
confidence: 99%
“…In other words, essentially the same band shape is obtained in the low-frequency range for polarized, depolarized, or without polarization selection of the scattered radiation. It is worth noting that the frequency-dependent depolarization ratio has been found in Raman spectra of high temperature molten salts, especially when complex molecular-like structures occur in the melt. ,, In the case of ionic liquids, the intermolecular vibrational dynamics has been much more investigated by OKE than low-frequency Raman spectroscopy. Both OKE and Raman spectroscopies probe polarizability fluctuations resulting from the molecular dynamics of the liquid, so that the spectral pattern of χ″(ω) is the same as the OKE spectra of ionic liquids.…”
Section: Vibrational Spectroscopy Of Pure Ionic Liquids In the Low-fr...mentioning
confidence: 99%
“…It is important to note that this behaviour can hardly be extended to zero frequency, since it was found that at frequencies below one-half or one-third of the boson maximum position this linear behaviour turns into a superlinear one [35]. We also note that there exists a difference in C(ν) for polarized and depolarized spectra [37], but in the range of the boson peak maximum this difference has marginal influence for the whole picture of C(ν) behaviour (for example, the polarized and depolarized C(ν) for SiO 2 glass are presented in [38], where it can be seen that this difference is not a dominant effect for the frequency dependence). Here it is remarked that the linear behaviour of C(ν) has been found for glasses with very different levels of the Debye contribution [35].…”
Section: Raman Coupling Coefficientmentioning
confidence: 68%
“…Low-energy excitations in amorphous solids and especially their presence and their dependence on external stimuli have been the subject of extensive experimental and theoretical examinations over the last years [23][24][25][26][27][28][29][30][31][32][33][34]. However, several aspects of low-energy excitations phenomenology are still under debate.…”
Section: The Boson Peak Regionmentioning
confidence: 99%
“…has led to the quest for phenomenological correlations which usually claim universal behavior for glasses. However, it has been shown that such correlations are not based on a well-established basis [25,26]. Another important spectral feature in the low-frequency Raman spectra of glasses is the quasielastic (QE) line with a characteristic width on the order of a few hundred GHz [23].…”
Section: The Boson Peak Regionmentioning
confidence: 99%